Ethical challenges of informed consent in patient related social media content - Yessy Andriani Fauziah; Eveline Yulia Darmadi; Dwi Setianiningtyas; Dian Agustin Wahjuningrum; Dany Agus Susanto; Farouk Al-Ghazaly (Universitas Airlangga, 2026)
Background: Social media has become a dominant platform for healthcare communication and promotion, particularly in aesthetic dentistry, where visual treatment outcomes are frequently shared. Patient photographs, procedural videos, and testimonials are widely used to attract public attention. However, traditional informed consent was primarily developed for clinical decision making and may not fully address the ethical implications of digital publication, including permanent online visibility, algorithm-driven dissemination, and potential secondary commercial use. Purpose: This literature review aims to analyze the ethical challenges associated with obtaining informed consent for patient-related social media content and to evaluate whether existing consent practices adequately protect patient autonomy, privacy, and professional integrity in digital environments. Reviews: Conventional informed consent emphasizes disclosure, comprehension, voluntariness, competence, and authorization. In the context of social media, additional concerns arise. Patients may experience subtle pressure to agree due to trust in the practitioner or fear of affecting their care relationship. Risk explanations often overlook long term digital exposure, uncontrolled redistribution, identity recognition despite anonymization, and reuse of content for marketing purposes. These issues create ethical tension between respect for autonomy, non-maleficence, beneficence, justice and professional responsibility. Current regulatory guidance in many settings does not clearly distinguish between clinical consent and consent for public digital dissemination. Conclusion: Existing informed consent models are insufficient to address the complexities of patient-related content on social media. A digitally adapted and transparent consent framework is essential to ensure voluntary participation, clear risk disclosure, and stronger protection of patient privacy in contemporary healthcare promotion.